Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan - Jessica Caren Witardjo, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this search is to examine empirical evidence the influence of profitability, leverage, firm size, and liquidity toward firm value on manufacturing companies listed in the Indonesia Stock Exchange in the period of 2016-2018. The sample in this research was determined by purposive sampling method. The research conducted by taking 74 manufacturing companies. The result of this research shows that profitability has a negative significant effect on firm value. Leverage, firm size, and liquidity have no significant effect on firm value.